2018
DOI: 10.3168/jds.2017-13459
|View full text |Cite
|
Sign up to set email alerts
|

Herd-level prevalence of the ultrasonographic lung lesions associated with bovine respiratory disease and related environmental risk factors

Abstract: Bovine respiratory disease complex (BRD) is a major calf disease during the preweaning period. Thoracic ultrasound (TUS) has been recently described as a reliable tool for assessing BRD-associated lung lesions. The objectives of this study were to define the herd-level prevalence of lung consolidation assessed by TUS (CONSTUS). A total of 39 Québec dairy herds were randomly chosen to participate in this cross-sectional study. Between 6 and 12 preweaned calves were examined for signs of CONSTUS defined by any s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
3
22
0
1
Order By: Relevance
“…Both Buczinski et al (2017) and Lago et al (2006) reported a gradual increase in prevalence from birth to the sixth and seventh week of life, respectively; we observed a similar rise in prevalence, which continued until 65 d of age (Supplemental Figure S1; https: / / doi .org/ 10 .3168/ jds .2018 -14773). The fact that most of the calves in the current study were housed outdoors may explain the lower prevalence observed of 6.9%, comparable to what Buczinski et al (2017) observed in the summer. Distributions of the percent of cases by age stratified by breed or region are shown in Supplemental Figures S2 and S3 (https: / / doi .org/ 10 .3168/ jds .2018 -14773), respectively.…”
Section: Prevalencesupporting
confidence: 68%
See 2 more Smart Citations
“…Both Buczinski et al (2017) and Lago et al (2006) reported a gradual increase in prevalence from birth to the sixth and seventh week of life, respectively; we observed a similar rise in prevalence, which continued until 65 d of age (Supplemental Figure S1; https: / / doi .org/ 10 .3168/ jds .2018 -14773). The fact that most of the calves in the current study were housed outdoors may explain the lower prevalence observed of 6.9%, comparable to what Buczinski et al (2017) observed in the summer. Distributions of the percent of cases by age stratified by breed or region are shown in Supplemental Figures S2 and S3 (https: / / doi .org/ 10 .3168/ jds .2018 -14773), respectively.…”
Section: Prevalencesupporting
confidence: 68%
“…Lago et al (2006) found a prevalence of 14.3% in 225 dairy calves housed in barns in the winter in Wisconsin and diagnosed with the Wisconsin BRD scoring system for preweaned calves. Buczinski et al (2017) found a median prevalence of 8% in the summer and 15% in the winter for lung consolidation diagnosed by ultrasound, consistent with BRD in preweaned calves in 39 dairy herds in Québec. Indoor housing and poor ventilation are associated with BRD, so the higher prevalence in the Wisconsin and Québec studies in the winter is not unexpected (Callan and Garry, 2002;Gorden and Plummer, 2010).…”
Section: Prevalencesupporting
confidence: 68%
See 1 more Smart Citation
“…First, the bacteria appears to be more prevalent in herds with larger groups of calves (>5 per pen). Group housing and increased number of animals per pen are well-known risk factors for respiratory disease (Buczinski et al, 2018), and perhaps this is related to M. haemolytica. Second, housing on sawdust appeared to be a risk factor for both the presence of M. haemolytica and H. somni.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in a previous study, BRSV and bPI3V infections were found in 71% and 80% of cow-calf farms respectively ( Assié et al, 2004b ). Furthermore, challenge trials do not reproduce the variability of host and environmental conditions that may be encountered in the field, such as variable passive immune transfer ( Raboisson et al, 2016 ), variable calf housing ( Assié et al, 2009 , Dubrovsky et al, 2019a , Maier et al, 2019 ) and variable seasonal or weather conditions ( Buczinski et al, 2018 , Dubrovsky et al, 2019b ). For these reasons, a multicentre study was chosen in order to reproduce this variability of environmental factors.…”
Section: Discussionmentioning
confidence: 99%